Age influences the circulating immune profile in pediatric sepsis - Fisler, Grace; Brewer, Mariana R.; Yaipen, Omar; Deutschman, Clifford S.; Taylor, Matthew D. (Frontiers in Immunology, 2025)
BackgroundThe immune response changes as patients age, yet studies on the immune dysregulation of sepsis often do not consider age as a key variable.ObjectiveWe hypothesized that age would influence the immune response in septic children and that there would be a distinct variation in the immune profile in healthy children and children with either sepsis, uncomplicated infection, or acute organ dysfunction without infection. We characterized the circulating immune profile of children presenting to our tertiary care children’s hospital.MethodsThis investigation was a prospective, observational cohort study that enrolled patients from July 2020 – September 2022. Patients were included if they were < 21 years, admitted to the PICU, and received fluid resuscitation and antibiotics. Peripheral blood mononuclear cells were isolated from samples collected on PICU day 1.ResultsEighty patients were enrolled. Children with sepsis had more regulatory CD4+ T cells and memory CD4+ T cells and less CD4+IL-10+ and CD8+T-bet+ T cells than healthy children. After ex vivo stimulation, sepsis samples had less of a reduction in CD4+ T cells producing IL-10 than healthy controls. Memory CD4+ T cells and regulatory CD4+ T cells were positively associated with age in sepsis alone.ConclusionA regulatory T cell failure may contribute to pediatric sepsis pathogenesis. Age is an important variable affecting sepsis-associated immune dysregulation and memory T cells in peripheral circulation correlate with age in sepsis alone.